Chemotherapy-induced nausea and vomiting: an overview and comparison of three consensus guidelines. Issue 1083 (11th November 2015) - Tageja, Nishant; Groninger, Hunter
Abstract: Chemotherapy-induced nausea and vomiting (CINV) remains one of the most debilitating toxicities associated with cancer treatment. In recent decades, significant strides have been made in our understanding of the pathophysiology of CINV, making way to more effective targeted pharmacotherapies, especially 5-hydroxytryptamine3 receptor antagonists and neurokinin-1 (NK-1) receptor antagonists. As much as 70%–80% of CINV can be prevented with appropriate administration of available antiemetics. Nevertheless, fear of CINV still may diminish cancer treatment adherence. To assimilate and summarise the rapidly growing body of clinical research literature on CINV, three professional organisations—the Multinational Association of Supportive Care in Cancer/European Society for Medical Oncology, the American Society of Clinical Oncology and the National Comprehensive Cancer Network—have created CINV management guidelines. While these respective guidelines are developed from similar consensus processes using similar clinical research literature, their results demonstrate several key differences in recommended strategies. This article aims to provide an overview of CINV pathophysiology, compare and contrast three expert guidelines and offer considerations for future clinical and research challenges.